KEKUATAN PEMBUKTIAN AKTA NOTARIS/PPAT SEBAGAI ALAT BUKTIDALAM PROSES PEMERIKSAAN SENGKETA PERDATA (Studi Kasus Putusan Nomor : 8/Pdt.G/2001/PN.Klt) - , SULASTRI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The thesis was intended to identify proofing power of notarial/PPAT deed as evident in civil dispute examination process and to study consideration of the judges in deciding the case. It was juridical empirical research that refers to field study to get primary data and supported with literary study. Literary study was conducted with documentary study, and field study was conducted through interview with respondents. The data was analyzed qualitatively with descriptive method. Based on the analysis, the conclusion is that resolution of civil dispute with evident of PPAT deed has perfect proving power and judges were bound with PPAT deed presented as the evident. Judges in their decision on case no.8/PDT.G/2000/PN.Klt state that suit of plaintiff was partly accepted and rejected others. Because main issue in the verdict is dispute on land, while suit of plaintiff accepted is on inheritance so suit of plaintiff is rejected. Plaintiff as losing party shall pay case expense emerging in the case